Agrogenic evolution of automorphic chernozems in the forest-steppe zone (Belgorod oblast) - Chendev, Yu. G.; Khokhlova, O. S.; Alexandrovskiy, A. L. (Eurasian soil science, 2017)
Agrochronosequences of chernozems with different periods of their use in rainfed farming with application of traditional technologies have been studied in a typical forest-steppe area in Belgorod oblast. Certain stages in the development of these soils during more than two centuries of their agricultural use have been identified. These stages are related to changes in the intensity and direction of soil forming processes, such as soil compaction, soil aggregation, dehumification of the upper horizons, calcification of the soil profiles, argillization, etc. A significant impact on the soil changes during the agrogenic evolution of chernozems is exerted by the digging activity of burrowers, which is especially pronounced in the old-arable chernozems.